Playful strategies and their contribution to the generation of new knowledge in university students - Cuadros-Solórzano, Marta Patricia; Cuadros-Solórzano, Gina Mercedes; Rodriguez-Gamez, Maria (International research journal of management, IT and social sciences, 2025)
The purpose of this article is to characterize the playful strategies that can be used to generate new knowledge among university students. The Desk Research methodology was used to review studies related to aspects that can promote knowledge generation, as well as to identify characteristics present in playful strategies that can facilitate the development of cognitive abilities and thinking styles in university students. It was determined that the application of playful strategies is indeed adequate for developing research skills and abilities in university students due to the training generated by repeating activities related to their future professional practice, in a motivating and low-stress environment.